Locus of Control : Teori Temuan Penelitian dan Reorientasinya dalam Manajemen Penanganan Kesulitan Belajar Peserta Didik - Syatriadin Syatriadin (FONDATIA, 2017)
The purpose of this research is to study the locus of control from the theoretical side, findings of research on locus of control in the context of education and learning and reorient it in management handling student learning difficulties. Using a qualitative, non-interactive approach with literary study methods. Methods of data analysis using meta-analysis with combination of content analysis and trend analysis techniques. The results showed that locus of control is one of the individual personality variables regarding belief in self-control over events experienced in self-determined life (internal locus of control) or controlled by the external locus of control. This theory was first proposed by Rotter which also offer the measurement and grouping instruments through Internal-External Scale. From a research perspective, the locus of control has an influence on the learning achievement of learners. Learners with internal locus of control have a better performance than the external group. Considering the importance of the focus of control in the development of education and learning, reorientation can be done by developing it in the management of learning difficulties. The process includes: identification of cases and problems, diagnosis, prognosis, remedial / referral, and evaluation and follow-up by integrating locus of control system.